WILL MANUFACTURING PERFORMANCE EVER IMPROVE IN NIGERIA AS EXPECTED? A CONSIDERATION WITH POVERTY IN FOCUS - Uduak Michael Ekong; Joseph John Umoinyang (Transpublika Publisher, 2024)
Despite efforts toward industrialization since 1960, Nigeria remains underdeveloped as of 2020 and may not achieve significant industrialization by 2040. Numerous investment policies have been implemented, yet poverty rates continue to rise. This study examines the responses of poverty to manufacturing sector performance in Nigeria, relying on country specific data from 1981 to 2022. The role of industrialization hung on the development and improvement of the manufacturing sector to reduce poverty. Historical evidences suggest that manufacturing performances had little impact on poverty reduction in Nigeria over the period. We used dynamic ordinary least squares (DOLS) techniques to show that manufacturing sector performance can reduced poverty by at least 9 percentage points at an instance of manufacturing performance growth albeit small. We argued for local content financial assistance as an effective financial model to manufacturing sector improvement for poverty reduction as an option against external finances as a policy option.